Formulae for the Generalized Drazin Inverse of a Block Matrix in Banach Algebras - Xiaoji Liu; Xiaolan Qin (Journal of Function Spaces)
We present some new representations for the generalized Drazin inverse of a block matrix in a Banach algebra under conditions weaker than those used in resent papers on the subject.